Potency Campaign Madurese Culture Through Gastronomy Diplomacy - Cholil, Ahmad; Rosyidi, Moch. Imron; Handaka, Tatag (ETTISAL : Journal of Communication, 2024)
Gastronomy is a very complex cultural product. The development of gastronomic tourism contributes to strengthening local identity, and will be an important point for the development of sustainable tourism. In gastro-tourism, the main motivation for someone to travel is to get the experience of tasting food and drinks that can provide impressions and memories throughout their life. This research aims to explain the role of gastronomy in campaigning for Madurese culture. This research was conducted using the Life Story method and a gastrodiplomacy study approach. The results of the research show that the eating tradition in Madura is almost carried out on various occasions, from human births to funeral ceremonies. The tradition of eating is a space for people to gather in various elements to exchange ideas and thoughts. The potential for gastronomy as a space for Madurese cultural campaigns is still very wide open. This is related to the unique gastronomic characteristics of Madurese food and can be an interesting topic of conversation at a meeting. This research suggests that it is applicable to hold activities such as MICE-Meeting Incentive Convention and Exhibition with a food theme to become a sustainable Madurese cultural space campaign .